An analysis of blends in local English newspapers / Komalata Manokaran - Komalata , Manokaran (2020)
Numerous blends are often found in the newspapers such as brunch (breakfast + lunch), chocoholic (chocolate + alcoholic), and brick-tacular (brick + spectacular). Blend is a type of word-formation technique combining two clipped words termed as source words (SWs). This qualitative study explores blends found in local English newspapers; they are The Star, News Straits Times, The Malay Mail, and The Borneo Post. The study aims to (1) classify types of blends and (2) analyse the differences between paradigmatic and syntagmatic in blends. This research uses two theories dealing with definition of blends and types of blends. The types of blends are studied based on Mattiello’s (2013) framework: morphotactic (total and partial blend), morphological and graphic (overlapping and non-overlapping) and morphosemantic (attributive and coordinative). Furthermore, the differences between paradigmatic and syntagmatic in blends are studied based on Bauer’s (2006, 2012) framework. Overall, 276 blends were selected to analyse their types of blends and semantic types (paradigmatic and syntagmatic) using a qualitative approach. The classifications of the paradigmatic and syntagmatic origin blend are based on their contextual meaning. The results reveal that the local English newspapers seem to be using more blends coined through the total blend and mostly are syntagmatic origin blends. The paper concludes that although there are many types of blends formed intentionally or unintentionally, the semantic types of blends determine the function of blends. Furthermore, the differences between paradigmatic and syntagmatic blends can be related as paradigmatic blends (shares same lexical class), while syntagmatic blends has two types termed as right-headed and left-headed. Syntagmatic blends mostly are endocentric, which means one of the SWs acts as a semantic head and the other SW as a modifier. The semantic relation defines the order of the two SWs. The semantic head always goes to the right side in blends, termed right-headed syntagmatic blends.